1991
DOI: 10.1523/jneurosci.11-08-02453.1991
|View full text |Cite
|
Sign up to set email alerts
|

Tau gene expression in rat sensory neurons during development and regeneration

Abstract: In the mature rat dorsal root ganglion (DRG), only one tau isoform is expressed, and this protein (110 kDa in apparent molecular weight) is considerably larger in size than the predominant tau isoforms found in brain. The size of the mRNA encoding the "big" tau mRNA in DRG [approximately 8 kilobases (kb)] is also much larger than that of the major rat brain tau mRNA species (approximately 6 kb). In this study, we examined the pattern of normal developmental changes in expression of this high-molecular-weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 36 publications
5
74
0
Order By: Relevance
“…Previous results suggested that HMW-tau may play a role in the specialization of the adult peripheral nervous system (27,28). For instance, HMW-tau and LMW-tau variants are expressed during development in the dorsal root ganglia, whereas only HMW-tau is present in the adult (28).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous results suggested that HMW-tau may play a role in the specialization of the adult peripheral nervous system (27,28). For instance, HMW-tau and LMW-tau variants are expressed during development in the dorsal root ganglia, whereas only HMW-tau is present in the adult (28).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, HMW-tau and LMW-tau variants are expressed during development in the dorsal root ganglia, whereas only HMW-tau is present in the adult (28). Since the mRNA in young and adult dorsal root ganglia migrates at 8-9 kb (27) and no 6-kb message is seen, LMW-tau and HMW-tau must be encoded by mRNAs larger than those in brain. Northern blots of rodent dorsal root ganglia using a probe for the nonhomologous region show hybridization to the 8-to 9-kb mRNA, indicating that exon 4a is expressed in normal When assayed with brain poly(A)+ RNA (5 jLg), the N-terminal fragment detected the tau transcript of 6 kb (lane 1), which is expressed in the central nervous system (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a shift in the balance of various tubulins and MAPS during regeneration may either increase or decrease the plasticity of the microtubule network during different phases of regeneration. Recent observations of downregulation of tau mRNA and protein levels in DRG neurons during regeneration provide support to this argument (Oblinger et al, 1991). Clearly, additional information will be required to sort out the mechanisms by which augmented or decreased levels of various tubulins and MAPS produce alterations in the functional properties of microtubule networks.…”
Section: Axotomy-induced Changes In And-tubandn Content In Drg Neuronsmentioning
confidence: 96%